2000
DOI: 10.1097/00124509-200003000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Responses to ECT in a Patient with Critical Aortic Stenosis

Abstract: We present a case study of a 46-year-old woman with a psychotic depressive illness of 2 months' duration with the coexisting medical diagnoses of critical aortic stenosis, severe labile hypertension, renal failure necessitating hemodialysis of 7-years' duration, and systemic lupus. Because of unresponsiveness to an antidepressant drug regimen, severe motor retardation, mutism, and refusal of food and fluids by mouth, an urgent indication for electroconvulsive therapy (ECT) was established. However, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The hyperdynamic state induced by sympathetic activation can be prevented by ganglion-blockers [46], betablockers [47][48][49][50][51][52][53][54][55][56][57][58][59]67,77], alpha-1 and alpha2-agonists [60][61][62][63][64][65][66], Ca2+-channel antagonists [68][69][70], nitrates [71][72][73][74][75][76] or local anesthetics [78]. Rapid, short-acting opioid [79][80][81] analgesics also possess sympatholytic effects and have recently been investigated as adjuvants during ECT.…”
Section: Drugs Used For Hemodynamic Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperdynamic state induced by sympathetic activation can be prevented by ganglion-blockers [46], betablockers [47][48][49][50][51][52][53][54][55][56][57][58][59]67,77], alpha-1 and alpha2-agonists [60][61][62][63][64][65][66], Ca2+-channel antagonists [68][69][70], nitrates [71][72][73][74][75][76] or local anesthetics [78]. Rapid, short-acting opioid [79][80][81] analgesics also possess sympatholytic effects and have recently been investigated as adjuvants during ECT.…”
Section: Drugs Used For Hemodynamic Stabilizationmentioning
confidence: 99%
“…Some case reports demonstrated that sodium nitroprusside, another peripheral-acting vasodilator, induced preventive effects on hyperdynamic changes [73][74][75]. In addition, Sudha et al [76] demonstrated the efficacy of 0.5 mg/kg of sodium nitroprusside administered intraperitoneally in increasing seizure duration in rats.…”
Section: Nitratesmentioning
confidence: 99%
“…These result in transient but quite significant hemodynamic changes, including an initial period of bradycardia [14], followed by a catecholamine surge with increases in blood pressure and heart rate that ordinarily resolve over several minutes after the seizure has ended [15]. Studies have shown the rate of ECT-associated cardiovascular complications to be 7.5% in patients without preexisting cardiovascular conditions, generally in the form of benign poststimulation transitory arrhythmias that resolved within minutes [16].…”
Section: Cardiovascular Complications Of Electroconvulsive Therapymentioning
confidence: 99%
“…Studies have reported a much higher rate (55%) of ECT-associated cardiovascular complications in patients with preexisting cardiovascular conditions [16]. Fortunately, most of these events also correspond to transitory arrhythmias that are self-correcting or controlled using β blockers such as esmolol (a short-acting selective β1 blocker) and labetalol (a nonselective β blocker and α1 blocker), which appear to attenuate effectively these acute hemodynamic responses, even in the setting of preexisting cardiovascular conditions [15,16]. In addition, according to one review, as many as 91% of these patients were able to safely complete their ECT courses [16].…”
Section: Cardiovascular Complications Of Electroconvulsive Therapymentioning
confidence: 99%
“…There has been 1 report of death in an SLE patient given ECT for severe psychotic depressive illness, however the death was resulting from a known complication of a pre-existing critical aortic stenosis in the patient. 18 ECT has also been reported to be of use in SLE patients with catatonia, 8,19Y21 including hyperkinetic and akinetic mutism. 22 More recently in 2010, Fam et al 10 reported the treatment of a case of NPSLE with catatonia with ECT in conjunction with cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%